La civilisation phénicienne et punique : manuel de recherche - Krings, Véronique. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1995)
This collective volume is devoted to the Phoenician and the Punic civilization studied for its own purpose but also for its relationship with contemporaneous cultures of the ancient Mediterranean. The first part discusses the various sources relating to the Phoenician and Punic world; a second part attempts to sum up the different facets of its material and cultural surrounding. The third part expounds the present state of our knowledge of the Phoenicians and the Punics in each of the large geographical areas where they have emerged. The work thus assembles clearly, conveniently and as completely as possible the basic facts that will allow specialists of fellow disciplines to initiate themselves, and well-informed researchers to complete or check easily their information. This volume includes a bibliography, illustrations, maps and indexes.